As contribuições das ciências humanas na formação inicial do professor de matemática: um olhar para a região oeste do Paraná - Gonçalves, Pamela (2017)
contributions for the initial formation of Mathematics teachers. The formation of teachers is one of the greatest challenges imposed on the education, not only for the Mathematics; and it has been object of researches, studies and reflections for the researchers who intend to understand the initial and continuing professional development paths. Simultaneously, it is supported the idea that the initial formation process must give enough theoretical and practical knowledge so that the future teacher can work properly in the social context in which he or she is nested. Being a teacher requires being prepared to face different everyday situations and understanding its social context, besides contributing to the development of the students’ citizenship. Based on this, the following question arose: what contributions do the Human Science bring for the initial formation of the Mathematics teachers, and how do these contributions are realized on Licenciature classroom courses? The aim of this research is to understand how prepared the Mathematics graduated teachers are, discussing how the Human Science can contribute (as knowledge and courses area) for the qualification of the teacher. Therefore, investigations about the opinions and views of the coordinators, the professors who teach the last year of the graduation, and the almost graduated students of the Mathematics classroom course, in the west of Paraná, were made. This research is based on the theories of researchers who research the teacher’s formation, mainly the formation of the Mathematics teacher. It is also based on the legal principles that direct the teacher’s formation in Brazil; and has historical information about Human Science and its contributions for the human being. The qualitative and quantitative methods of researching are the ones present in this research, for the writing strategies and for analyzing the data. The orientations twhearte a brea simedp oinrt aBnatr fdoinr t(h2is0 1re1s),e tahricsh i,s t haels oM aa tdheomcuamtice nctoaul rrsees enaorrcmhs, i(tL aDnBa)ly, sthees Pthoeli tliacwals- Pedagogical Projects and the Curriculum Frameworks of the courses. For the field research, the coordinators and professors of the course answered a semi structured interview, and the students answered a questionnaire. The results obtained show that it is necessary to implement a new structure on this course, so it become possible to have Human Science contents implemented in the courses of the graduation and in the acting of the professors. Another result gotten is related to the dichotomy between the areas known as Pure Mathematic and Education Mathematic, what could be realized on the interviewees’ speech and can be found in the literature, a fact that seems to be kept year after year in the courses. In order to improve the current reality mentioned, we suggest to propose training the Mathematic teachers for a great and continuing formation, which includes a better humanized teaching of the Exact Science, using methodologies that allows to integrate and promote courses of specific subjects so that reflections about human relations, social relations and citizenship improvement can be taught together with. It would result on the development and improvement of the abilities the college students need in order to reflect about “being a teacher”, what aims to get prepared to work at the educational system, since our acting influence others and include responsibility and citizenship aspects on the process of teaching people of different generations.